ACUTE TOXICITY TEST AND EVALUATION OF ANALGESIC AND ANTI-INFLAMMATORY ACTIVITIES OF METHANOL LEAF EXTRACT OF OCHNA KIBBIENSIS HUTCH AND DALZ (OCHNACEAE) - Muhammad, Abubakar Alhaji; Ismaila, Abdullahi Musa; Yusuf, Amina Jega; Sani, Yahaya Muhammad; Ibrahim, Nasir; Buhari, Muhammad Koko; Isah, Abdullahi (FUDMA JOURNAL OF SCIENCES, 2025)
Pain is an unpleasant feeling caused by the stimulation of pain receptors. Inflammation is a complex response to exogenous and endogenous stimuli. Ochna kibbiensis Hutz and Dalz (Ochnaceae) is majorly used traditionally in the treatment of pain, inflammation and malaria. This study aimed to evaluate the analgesic and anti-inflammatory properties of the leaf extract of the plant. The analgesic activity of the Methanol leaf extract (MLE) was evaluated using acetic acid-induced writhing in mice and formalin-induced pain in rat models while the anti-inflammatory studies were carried out using formalin-induced inflammation in rats. In the acetic acid model, the MLE in graded doses (40, 80 and 160 mg/kg) significantly (p0.05) and in a concentration-dependent manner reduced the number of writhes induced by acetic acid. Similarly, the extract significantly (p0.05) reduced pain induced by formalin in both phases, with the highest dose (160 mg/kg) having a higher % inhibition than the standard drug, Piroxicam (10 mg/kg). In the formalin-induced inflammation test in rats, at the fourth hour, all the doses significantly (p0.05) in a concentration-dependent manner reduced the paw oedema of the rat. To the best of our knowledge, this is the first report of the evaluation of the analgesic and anti-inflammatory activities of the methanol leaf extract of O. kibbiensis.